PENGARUH VISUAL MERCHANDISING, FASHION INVOLVEMENT TERHADAP IMPULSE BUYING DENGAN POSITIVE EMOTION SEBAGAI VARIABEL MEDIASI (Survei pada Konsumen Distro Nimco Mega Store di Surakarta) - Evan Candra Wijaya; Marjam Desma Rahadhini; Edi Wibowo (Universitas Slamet Riyadi, 2020)
This research was conducted on consumers Nimco Mega Store Distro in Surakrta, the type of data used is qualitative and quantitative data. Data sources used are secondary and primary data. The entire population in this study are all Nimco Distro consumers whose numbers cannot be known. The sample used in this study was taken as many as 100 respondents. The sampling technique is done by using non-probability sampling using purposive sampling method. In this study shows that visual merchandising and fashion involvement significantly influence positive emotion. Variable visual merchandising, fashion involvement, and positive emotion have a significant effect on impulse buying. The sobel test results in this study indicate that visual merchandising and fashion involvement influence impulse buying with positive emotion as a mediating variable.